A study on the relationship between level of anxiety in communication and level of language proficiency among UiTM TESL final semester students / Ezzah Amani Mohamad Radzi - Mohamad Radzi, Ezzah Amani (Faculty of Education, 2013)
Communicating in English has been an important aspect in moving forward in one's career especially in Malaysia. However there are many graduates who have failed to do so particularly during interviews. There can be many reasons as to why this happens and one of the reasons may be due to their high level of anxiety which may be caused by their low level of proficiency in the language. This paper aims to study the relationship between the level of anxiety and the language proficiency of UiTM TESL (Teaching English as A Second Language) final semester students. The methods used to cam7 out this study are by distributing a questionnaire to measure their proficiency; Paul Nation's Vocabulary Size Test, as well as a questionnaire to measure their level of anxiety; FLCAS (Foreign Language Classroom Anxiety Scale). An interview was also carried out to support the findings from the questionnaires. The questions asked were of a one dimensional situation; their classroom environment. It was found in this study that there is a weak negative correlation between level of anxiety and level of proficiency. Being proficient/not proficient in the language does not make the participants less anxious/anxious in communicating. However, it can be confirmed that the participants would feel anxious in certain situations like being interviewed by people whom they are not comfortable with and whom they perceive to be sceptical.